Carbon fiber bundle and method for producing the same

By controlling fiber diameter variation and applying a sizing agent, the carbon fiber bundle achieves improved abrasion resistance and yarn strength, ensuring high process stability and performance in CFRP pressure vessels.

JP2025020078APending Publication Date: 2025-02-12TEIJIN LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123920
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-30
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

Carbon fiber bundles used in CFRP pressure vessels suffer from fuzziness and thread breakage during the filament winding molding process, which compromises the reflection of their high mechanical properties in the final product.

Method used

The carbon fiber bundle is characterized by a specific fineness, tensile strength, and coefficient of variation of fiber diameters, with a controlled ratio of fibers having diameters less than 85% of the average, and a spreading width of 0.0180 mm/Tex or more, along with streak-like unevenness and a sizing agent for improved abrasion resistance.

Benefits of technology

The solution enhances the carbon fiber bundle's resistance to abrasion and yarn breakage, ensuring high process stability and performance of CFRP pressure vessels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020078000001
    Figure 2025020078000001
Patent Text Reader

Abstract

To provide a carbon fiber bundle having high abrasion resistance and thread breakage resistance.SOLUTION: There is provided a carbon fiber bundle having a sizing agent attached thereto, which is obtained by controlling: a fineness into 800 to 3000 Tex; the number of single fibers into 20000 to 50000 pieces; a coefficient of variation of a fiber diameter of each single fiber into 10% or less; a ratio of single fibers with a fiber diameter less than 85% of the average fiber diameter into 3.0% or less; a value obtained by dividing a thread width (mm) when rewound with a tension of 1 N by the fineness (Tex) into 0.0180 mm / Tex or more; and a tensile strength into 5600 MPa or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon fiber bundle and a manufacturing method thereof, and more particularly to a carbon fiber bundle suitable for manufacturing a pressure vessel made of carbon fiber reinforced plastic (CFRP) and a manufacturing method thereof. [Background technology]

[0002] CFRP, which is made of carbon fiber and matrix resin, is widely used in various fields such as general industry, automobiles, sports and leisure, and aerospace due to its high specific strength and specific rigidity, and the industrial applications of these CFRPs have been expanding in recent years. As the applications of CFRP expand, there is also a growing demand for manufacturing methods of CFRP that can express high composite properties.

[0003] CFRP has excellent mechanical properties, and as its price has fallen it is being used to replace metal materials. Taking advantage of its light and strong characteristics, CFRP is being actively developed for use in repair materials for concrete structures, wind turbine blades, structural materials such as bodies and shafts for transportation vehicles, various pressure vessels, etc. CFRP pressure vessels are manufactured by the filament winding molding method (hereinafter also referred to as the "FW molding method"), in which carbon fiber bundles impregnated with a matrix resin are wound around the outer surface of a liner, which serves as the core material. This FW molding method has been widely adopted when manufacturing pressure vessels using glass fibers, but it is also adopted when manufacturing pressure vessels using carbon fibers. However, there is a problem with pressure vessels manufactured using carbon fibers by the FW molding method in that the excellent fiber properties of carbon fibers are not fully reflected.

[0004] Carbon fiber bundles are prone to fuzzing and thread breakage due to friction with fixed guides, rollers, etc. during processing. Fuzzing and thread breakage of carbon fiber bundles not only deteriorates processability and process stability, but also adversely affects the performance of CFRP, which is the final molded product. In other words, if fuzzing or thread breakage occurs in the carbon fiber bundle, the excellent physical properties of the carbon fiber bundle, which has high tensile strength, cannot be fully reflected in the performance of the CFRP. Therefore, carbon fiber bundles are required to have resistance to abrasion and thread breakage.

[0005] Patent Document 1 discloses a carbon fiber precursor fiber in which the Z-average molecular weight Mz(F) of the polyacrylonitrile polymer constituting the fiber is 600,000 to 2,000,000, the polydispersity Mz(F) / Mw(F) (Mw(F) represents the weight-average molecular weight of the polyacrylonitrile polymer constituting the fiber) is 2 to 5, the root-mean-square roughness Rms measured in a range of 3 μm with an atomic force microscope is 15 to 40 nm, the single fiber fineness is 0.3 to 1.5 dtex, and the coefficient of variation of the single fiber cross-sectional diameter is 0 to 5%. This carbon fiber precursor fiber has a small variation in fiber diameter, but requires the use of an ultrahigh molecular weight polymer and cannot have a large number of single yarns in a fiber bundle, which is not cost-effective. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-255159 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a carbon fiber bundle having high abrasion resistance and fiber breakage resistance. Another object of the present invention is to provide a method for producing such a carbon fiber bundle. [Means for solving the problem]

[0008] As a result of intensive investigations into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by setting the coefficient of variation of fiber diameters of single fibers constituting a carbon fiber bundle to a predetermined value or less, setting the number of single fibers having a fiber diameter of 85% or less of the average fiber diameter to a predetermined value or less, and setting the carbon fiber bundle to a predetermined tensile strength, and have thus completed the present invention.

[0009] The present invention, which solves the above problems, is as described below.

[0010] [1] A carbon fiber bundle having a sizing agent attached thereto, The average fineness is 800~3000Tex. The number of single yarns is 20,000 to 50,000. The coefficient of variation of the fiber diameter of each single fiber is 10% or less; The ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less, The value obtained by dividing the yarn width (mm) by the fineness (Tex) when rewound under a tension of 1N is 0.0180mm / Tex or more, A carbon fiber bundle having a tensile strength of 5600 MPa or more.

[0011] [2] The carbon fiber bundle according to the above [1], wherein each of the single fibers constituting the carbon fiber bundle has stripe-like irregularities on its surface along the fiber axis direction.

[0012] [3] Knot strength: 600-800N / mm 2 The carbon fiber bundle according to [1] or [2] above, wherein the range is

[0013] [4] The carbon fiber bundle according to any one of [1] to [3] above, which is for filament winding molding.

[0014] [5] The carbon fiber bundle according to any one of [1] to [4] above, which is used as the reinforcing fiber of a pressure vessel in which an outer periphery of a metal or resin liner is covered with a fiber-reinforced plastic shell made of reinforcing fibers and resin.

[0015] The invention described in [1] above is a carbon fiber bundle having a predetermined fineness and number of single fibers, small variation in fiber diameter, a small ratio of single fibers having a fiber diameter significantly below the average fiber diameter, and a large value obtained by dividing the yarn width (mm) by the fineness (Tex) when rewinding with a tension of 1 N (meaning yarn width / fineness; hereinafter also referred to as spread width). In the invention described in [2] above, each single fiber constituting the carbon fiber bundle has streaky irregularities on its surface along the fiber axis direction. The presence of these streaky irregularities means that the carbon fiber precursor fiber, which is the raw material of the carbon fiber, is produced by a wet spinning method. The invention described in [3] above is a carbon fiber bundle having knot strength within a predetermined range, high strength against bending stress and compressive stress, and excellent processability. Since there is little occurrence of yarn breakage and fluff, it is particularly suitable for use as a reinforcing fiber for pressure vessels manufactured by filament winding molding, for example, as described in [4] and [5] above.

[0016] [6] Carbon fiber precursor fiber bundles are flame-retarded, The fineness is 1600~6000Tex. The number of single yarns is 20,000 to 50,000. The coefficient of variation of the fiber diameter of each single fiber is 10% or less; Obtaining a flame-resistant fiber bundle in which the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less; The method for producing a carbon fiber bundle according to [1], further comprising the steps of: carbonizing the flame-resistant fiber bundle;

[0017] [7] The method for producing a carbon fiber bundle according to [6], wherein the carbon fiber precursor fiber bundle is produced by a wet spinning method.

[0018] The inventions described in [6] and [7] above are methods for producing carbon fiber bundles using flame-resistant fiber bundles having a predetermined fineness and number of single fibers, small variation in fiber diameter, and a small ratio of single fibers having a fiber diameter significantly smaller than the average fiber diameter. Effect of the Invention

[0019] The carbon fiber bundle of the present invention has high resistance to abrasion and fiber breakage, and is therefore particularly suitable for FW molding. BEST MODE FOR CARRYING OUT THEINVENTION

[0020] The carbon fiber bundle and the method for producing the same of the present invention will be described below.

[0021] (1) Carbon fiber bundle The carbon fiber bundle of the present invention is a carbon fiber bundle having a sizing agent attached thereto, characterized in that it has a fineness of 800 to 3000 Tex, a number of single fibers of 20,000 to 50,000, a coefficient of variation of fiber diameter of each single fiber of 10% or less, a ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter of 3.0% or less, a value obtained by dividing the yarn width (mm) when rewound under a tension of 1 N by the fineness (Tex) of 0.0180 mm / Tex or more, and a tensile strength of 5600 MPa or more.

[0022] The carbon fiber bundle is not particularly limited, and may be a pitch-based, rayon-based, polyacrylonitrile (PAN)-based carbon fiber bundle, etc. In order to particularly improve operability, processability, and mechanical strength, a PAN-based carbon fiber bundle is preferred.

[0023] The fineness of the carbon fiber bundle is 800 to 3000 Tex, preferably 800 to 2500 Tex, and particularly preferably 800 to 2000 Tex. If it is less than 800 Tex, the productivity is poor, and if it exceeds 3000 Tex, the strength of the carbon fiber bundle decreases, or a carbon fiber bundle having sufficient strength cannot be obtained with good productivity due to heat accumulation breakage during the flame-resistant process.

[0024] The number of single fibers of the carbon fiber bundle is 20,000 to 50,000, preferably 24,000 to 48,000, and more preferably 30,000 to 48,000. By having 20,000 or more, the production efficiency of the carbon fiber bundle and the production efficiency of the composite material by the FW method can be improved. By having 50,000 or less, a high-strength carbon fiber bundle can be easily obtained.

[0025] The coefficient of variation of the fiber diameter of each single fiber in the carbon fiber bundle is 10% or less, preferably 3.0 to 10.0%, more preferably 5.0 to 8.0%, and particularly preferably 5.0 to 7.0%. If it exceeds 10%, the strength varies greatly within the carbon fiber bundle, making it difficult to increase the strength of the composite material. In addition, fuzz is likely to occur due to breakage of the single fibers during FW molding.

[0026] The ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less, preferably 0.1 to 3.0%, and particularly preferably 0.1 to 2.0%. If it exceeds 3.0%, the locations where single fibers with small fiber diameters exist tend to become the starting points of fracture of the composite material, making it difficult to increase the strength of the composite material. In addition, during FW molding, single fibers with small fiber diameters tend to break and generate fluff. Therefore, even if a high-strength carbon fiber bundle is used, the fiber properties are not fully reflected in the properties of the composite material.

[0027] The ratio of yarn width (mm) / fineness (Tex) (also called spread width) when rewound under a tension of 1 N is 0.0180 mm / Tex or more, preferably 0.0180 to 0.0500 mm / Tex, and more preferably 0.0200 to 0.0300 mm / Tex. If it is less than 0.0180 mm / Tex, a sufficient spread width of the fibers cannot be obtained when manufacturing a pressure vessel, and gaps are generated between the carbon fiber bundles, which tends to deteriorate the performance of the pressure vessel.

[0028] The tensile strength of the carbon fiber bundle is 5600 MPa or more, preferably 5600 to 6600 MPa, and particularly preferably 5700 to 6500 MPa. By having a tensile strength of 5600 MPa or more, it is easy to achieve weight reduction while maintaining the strength of a composite material produced using the same.

[0029] The knot strength of the carbon fiber bundle is 600 to 800 N / mm 2 It is preferable that the strength is 650 to 800 N / mm 2 More preferably, it is 680 to 800 N / mm 2 More preferably, the resistance is 600 to 800 N / mm 2 If so, the amount of fluff generated during the manufacturing process will be small, and high-level processability will be excellent.

[0030] In the carbon fiber bundle of the present invention, each single fiber constituting the carbon fiber bundle preferably has streak-like irregularities on its surface along the fiber axis direction. By having streak-like irregularities, it is expected that the adhesion to the matrix resin can be improved. The streak-like irregularities are formed by producing the carbon fiber precursor fiber, which is the raw material of the carbon fiber, by a wet spinning method.

[0031] The carbon fiber bundle of the present invention has a sizing agent attached thereto. The amount of the sizing agent attached is preferably 0.4 to 1.4% by mass, more preferably 0.5 to 1.2% by mass. When the amount of the sizing agent is less than 0.4% by mass, the fiber opening property is improved, but the abrasion resistance to guides, rollers, etc. during the process is likely to decrease. When the amount of the sizing agent is more than 1.4% by mass, the fiber opening property is deteriorated and a large amount of the sizing agent is present at the interface between the resin and the carbon fiber when the bundle is made into a pressure vessel, which may result in a low burst pressure in a burst test. The sizing agent means the active ingredient of the sizing agent remaining in the final carbon fiber bundle. The solvent, such as water, which is removed in a later process is not included in the mass of the sizing agent.

[0032] The sizing agent is preferably selected according to the matrix resin used in the composite material. For example, epoxy resin, epoxy-modified polyurethane resin, polyester resin, phenol resin, polyamide resin, polyurethane resin, polyimide resin, polyvinyl alcohol resin, polyvinylpyrrolidone resin, polyethersulfone resin, etc. can be used alone or in combination of two or more kinds. Among these, from the viewpoint of adhesion to the matrix resin, it is preferable to use thermoplastic resins such as polyester resins, polyamide resins, polyimide resins, and polyethersulfone resins, more preferably polyamide resins, and particularly preferably copolymerized polyamides.

[0033] Moreover, the sizing agent used in the present invention is preferably a sizing agent that is solid at 25° C. When a sizing agent that is solid at 25° C. is used, the sizing agent is less likely to adhere to rollers or guides when the fiber bundle to which the sizing agent is attached is transported by rollers, etc., so that the generation of fluff in the production process can be suppressed and a carbon fiber bundle with even higher abrasion resistance can be obtained. The preferred melting point of the active ingredient of the sizing agent is 60 to 140°C.

[0034] The carbon fiber bundle of the present invention is preferable for use as a reinforcing fiber in filament winding molding, which will be described later.

[0035] (2) Manufacturing method of carbon fiber bundle The carbon fiber bundle of the present invention can be produced by the following method. First, a spinning dope is spun to obtain a carbon fiber precursor fiber bundle, the carbon fiber precursor fiber bundle is flame-retarded to obtain a flame-resistant fiber bundle, and then the flame-resistant fiber bundle is carbonized to obtain a carbon fiber bundle.

[0036] The precursor fiber used for producing carbon fiber is preferably a PAN-based fiber. Specifically, the PAN-based fiber is preferably produced by spinning a spinning dope containing 90% by mass or more, preferably 95% by mass or more of acrylonitrile and 10% by mass or less of other monomers, either alone or as a copolymer, from a spinneret. Examples of the other monomers include itaconic acid, fumaric acid, and (meth)acrylic acid esters.

[0037] A wet spinning method is preferred as a spinning method for the carbon fiber precursor fiber bundle. By adopting the wet spinning method, stripe-like irregularities can be formed along the fiber axis direction on the surface of each single fiber constituting the finally obtained carbon fiber bundle. The spinning dope is preferably a solution in which the acrylic polymer is dissolved in a 30 to 60 mass % zinc chloride solution. The viscosity of the spinning dope is preferably 3 to 100 Pa·s.

[0038] The spinning dope may be filtered to remove impurities from it, which contributes greatly to stabilizing the process and improving strength, elasticity, etc.

[0039] In order to produce the carbon fiber bundle of the present invention, it is necessary to set the coefficient of variation of the fiber diameter in the above-mentioned range and the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter in the precursor fiber bundle stage to the above-mentioned range. To achieve this, it is effective to make the draft rate in each single fiber uniform. In order to make the draft rate uniform, it is effective to use a spinneret with a small number of spinning holes or to uniform the tension received by each single fiber under the spinneret by arranging the spinning holes in a doughnut shape, etc. As such a spinneret, the spinneret described in JP 2022-173821 A can also be used.

[0040] The number of spinneret holes is preferably 10,000 to 50,000, and more preferably 12,000 to 36,000. If the number of spinneret holes is less than 10,000, it is necessary to combine fibers obtained from a plurality of spinnerets in order to obtain a fiber bundle consisting of 20,000 to 50,000 single fibers as the object of the present invention, and the more the number of spinnerets increases, the greater the influence of the variation between the fibers, resulting in a large variation in fiber diameter in the obtained carbon fiber bundle. In addition, if the number of spinneret holes exceeds 50,000, it is difficult to uniformly discharge the spinning dope, and the variation in fiber diameter also increases.

[0041] The draft ratio when the spinning dope is discharged from the spinneret needs to be adjusted depending on the type of spinning dope and the spinneret used. When using a spinneret with many spinning holes, if the draft ratio is too high, the variation in fiber diameter of the single fiber tends to increase. As an example, the draft ratio (surface speed of the take-up roller / discharge linear speed) when using the acrylic polymer spinning dope used in Example 1 described later is preferably 14 to 40% when the number of spinning holes is 12000 or less, 14 to 30% when the number of spinning holes is more than 12000 and 18000 or less, and 14 to 28% when the number of spinning holes is more than 18000. If it deviates from this range, the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter tends to increase. That is, when an acrylic polymer spinning dope is used (when the final carbon fiber is a PAN-based fiber), When the number of spinning holes is 12,000 or less, the draft rate is 14 to 40%. When the number of spinning holes is more than 12,000 and less than 18,000, the draft rate is 14 to 30%. When the number of spinning holes is over 18,000, the draft rate is 14 to 28%. It is preferable to spin the fiber bundle under the above conditions, and it is preferable to use the carbon fiber precursor fiber bundle produced under such conditions as a raw material for the flame-resistant fiber bundle.

[0042] The precursor fiber bundle is washed and wet heat stretched while being subjected to tension, and the total stretch ratio in the washing and wet heat stretching steps is preferably 10 to 15 times.

[0043] The obtained carbon fiber precursor fiber bundle is subsequently heat-treated (flameproofing treatment) in heated air at 220 to 300° C., preferably 230 to 260° C., to obtain a flameproof fiber bundle. This treatment is generally performed at a draw ratio in the range of 0.85 to 1.30, but in order to obtain a carbon fiber bundle with high strength and high elastic modulus, a draw ratio of 0.95 to 1.30 is more preferable.

[0044] The flame-resistant fiber bundle obtained by subjecting the above-mentioned carbon fiber precursor fiber bundle to flame-resistant treatment is The fineness is 1600~6000Tex. The number of single yarns is 20,000 to 50,000. The coefficient of variation of the fiber diameter of each single fiber is 10% or less; It is necessary that the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less.

[0045] The fineness of the flame-resistant fiber bundle is 1600 to 6000 Tex, preferably 2000 to 5000 Tex, and particularly preferably 2500 to 3500 Tex. If it is less than 1600 Tex, the productivity is poor, and if it exceeds 6000 Tex, heat accumulation breakage may occur during the flame-resistant process. In addition, the strength of the carbon fiber bundle obtained by carbonizing this flame-resistant fiber bundle may decrease.

[0046] The number of single filaments of the flame-resistant fiber bundle is 20,000 to 50,000, preferably 24,000 to 48,000, and more preferably 30,000 to 48,000. By having 20,000 or more, the production efficiency of the carbon fiber bundle and the production efficiency of the composite material by the FW method can be increased. By having 50,000 or less, the carbon fiber bundle obtained by carbonizing this flame-resistant fiber bundle is likely to have high strength.

[0047] The coefficient of variation of the fiber diameter of each single fiber constituting the flame-resistant fiber bundle is 10% or less, preferably 3.0 to 10.0%, more preferably 5.0 to 8.0%, and particularly preferably 5.0 to 7.0%. If it exceeds 10%, heat storage breakage may occur during the flame-resistant process. In addition, the strength of the single fiber in the carbon fiber bundle obtained by carbonizing this flame-resistant fiber bundle varies greatly, and it is difficult to increase the strength of the composite material even if it is used as a reinforcing fiber.

[0048] The ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter of each single fiber constituting the flame-resistant fiber bundle is 3.0% or less, preferably 0.1 to 3.0%, and particularly preferably 0.1 to 2.9%. If it exceeds 3.0%, the location where the single fibers having a small fiber diameter exist is likely to become the starting point of destruction in the composite material finally obtained, making it difficult to increase the strength of the composite material. In addition, in the carbon fiber bundle obtained by carbonizing this flame-resistant fiber bundle, the single fibers having a small fiber diameter are likely to break and generate fluff during FW molding. Therefore, even if a high-strength carbon fiber bundle is used, the fiber properties are unlikely to be fully reflected in the properties of the composite material.

[0049] The flame-retardant fiber bundle is carbonized by a conventional method. For example, the temperature is raised in an inert gas atmosphere such as nitrogen or argon, preferably in an inert gas atmosphere with an oxygen concentration of less than 0.05 ppm by volume, and the temperature is gradually increased in a carbonization furnace while controlling the tension of the flame-retardant fiber bundle to perform firing. The firing temperature is preferably 600 to 2000°C, and particularly preferably 1000 to 1700°C. As the inert gas, nitrogen is preferred because it is inexpensive.

[0050] It is also preferable to perform a surface treatment after the carbonization treatment. The method of the surface treatment is not particularly limited, but liquid phase oxidation using a chemical solution, electrolytic oxidation in which the carbon fiber is electrolytically treated as the anode in an electrolyte solution, gas phase oxidation in which plasma treatment is performed in a gas phase state, etc. can be used. Among these, electrolytic oxidation is preferably used from the viewpoints of productivity, uniformity of treatment, and safety. The electrolyte of the electrolyte used in the electrolytic treatment is not particularly limited, but inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, boric acid, and carbonic acid; organic acids such as acetic acid, butyric acid, oxalic acid, acrylic acid, and maleic acid; ammonium salts or ammonia such as ammonium sulfate, ammonium hydrogen sulfate, ammonium nitrate, ammonium hydrogen nitrate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium carbonate, and ammonium hydrogen carbonate; alkali hydroxides such as sodium hydroxide, potassium hydroxide, and barium hydroxide; inorganic salts such as sodium carbonate, sodium hydrogen carbonate, sodium phosphate, and potassium phosphate; organic salts such as sodium maleate, sodium acetate, potassium acetate, and sodium benzoate; can be used alone or as a mixture of two or more kinds.

[0051] The temperature of the electrolytic solution is preferably 0 to 100°C, and more preferably 25 to 45°C. The concentration of the electrolyte is preferably 5 to 25% by mass, and more preferably 8 to 12% by mass. The electrolytic treatment is preferably carried out using a plurality of electrolytic cells. Considering the equipment, costs, and the complexity of setting conditions, it is preferable to use 2 to 10 cells. The quantity of electricity is preferably 0.5 coulombs or more, and more preferably 2 to 100 coulombs per 1 g of carbon fiber.

[0052] A sizing agent is applied to the carbon fiber bundle of the present invention in order to improve the abrasion resistance. The sizing agent has already been described. The sizing agent may be applied by a known method, for example, a method of immersing the carbon fiber bundle in a sizing agent bath. The above-mentioned fiber spread width can be controlled by adjusting the type and amount of the sizing agent.

[0053] (3) Manufacturing method of pressure vessels using FW molding A pressure vessel can be manufactured by winding the carbon fiber bundle of the present invention around a liner or the like while impregnating the bundle with a resin, and then curing the resin.

[0054] In this FW molding method, the carbon fiber bundles are easily damaged by friction with rollers and guides during the process. Damage to the carbon fiber bundles not only reduces the process passability and process stability, but also reduces the performance of the obtained carbon fiber composite material. The carbon fiber bundle of the present invention has a uniform ratio of single fibers having a fiber diameter less than 85% of the average fiber diameter of 3.0% or less, so that even if friction with rollers or guides occurs, fluffing and thread breakage are unlikely to occur.

[0055] The resin is preferably impregnated while opening the sizing-agent-attached carbon fiber bundles using an opening roller or the like. The resin (matrix resin) is preferably a thermosetting resin. For example, epoxy resin, unsaturated polyester resin, vinyl ester resin, and phenol resin can be used. In addition, additives such as a curing agent and a defoaming agent may be added to the resin. The curing temperature, curing time, and the like are conventionally known and are appropriately adjusted depending on the resin used.

[0056] This paper describes a method for manufacturing a CFRP pressure vessel in which the outer surface of a metal or resin liner is covered with a fiber-reinforced plastic shell made of resin and carbon fiber used as reinforcing fibers. In the method for manufacturing a pressure vessel, a fiber reinforced resin layer (hoop layer) in which resin-impregnated sizing agent-attached carbon fiber bundles (hereinafter also referred to as "resin-impregnated carbon fiber bundles") are arranged so as to wrap around the axis of the liner, and / or a fiber reinforced resin layer (helical layer) in which resin-impregnated carbon fiber bundles are arranged helically with respect to the axial direction of the liner is laminated on the outer surface of a metal or resin liner having a hollow portion. The laminate configuration of the fiber reinforced resin layer (hoop layer) and / or fiber reinforced resin layer (helical layer) is appropriately determined depending on the desired performance of the pressure vessel.

[0057] Thereafter, the resin impregnated in the resin-impregnated carbon fiber bundle is cured by a curing method appropriate for the resin, to produce a CFRP pressure vessel. The CFRP pressure vessel manufactured in this manner fully reflects the excellent fiber properties of the carbon fiber bundles. The actual burst pressure of the CFRP pressure vessel manufactured by this manufacturing method relative to the theoretical burst pressure is preferably 85% or more, more preferably 90% or more, and particularly preferably 95% or more. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. The evaluation methods used in the examples are as follows.

[0059] [Average fiber diameter of single fibers, coefficient of variation of fiber diameter of single fibers, and ratio of single fibers having a fiber diameter less than 85% of the average fiber diameter] The cross section of the fiber bundle was image-analyzed to measure the fiber diameter and the coefficient of variation of each fiber. Specifically, the precursor fiber bundle or the carbon fiber bundle was embedded in resin, and then cut perpendicularly to the fiber axis to prepare a test piece, and the cut surface was polished with a polishing machine. The polished surface was observed at multiple points with a microscope at a magnification of 400 times, and the fiber diameter was measured by image processing. The number of single fibers measured was 3% to 10% of the total number of single fibers in the fiber bundle. From these measurements, the average fiber diameter and the coefficient of variation of the fiber diameter were calculated. Coefficient of variation = standard deviation / mean From the results of the above measurements, the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter was calculated.

[0060] [Strength of resin-impregnated carbon fiber bundle strand] The strength of the resin-impregnated strand of the carbon fiber bundle with the sizing agent was measured according to the method specified in JIS·R·7608.

[0061] [Carbon fiber knot strength] Knot strength was measured according to the method specified in JIS·L·1015.

[0062] [Spreading width] The carbon fiber bundle wound on the bobbin was unwound at a speed of 10 m / min under a tension of 1 N, passed over a free roller, and then wound around a drum. The yarn width (mm) when wound around the drum was measured at 90 different locations, and the average yarn width was calculated. The spread width was calculated from this average yarn width and the fineness of the carbon fiber using the following formula. Spread width = Average yarn width (mm) / Fineness (Tex)

[0063] [Abrasion evaluation] A 50mm diameter SUS304 guide was fixed, and a carbon fiber bundle wound on a bobbin was unwound on the guide surface at a speed of 10m / min with a tension of 1N. After running the bundle on the guide for 30 minutes, the mass of the carbon fiber fluff adhering to the guide surface was measured. The fluff mass was designated a (μg), the mass of the running carbon fiber bundle was designated b (g), and the value of c=a / b was used to evaluate the following criteria. ○: c ≦0.1, △: 0.1< c <0.5, ×:c ≧ 0.5

[0064] [Method of evaluating the burst pressure of pressure vessels] A carbon fiber bundle was impregnated with a resin composition having the following resin composition around the outer surface of a cylinder-shaped aluminum liner having a length of 504 mm, an outer diameter of 160 mm, and a thickness of 2 mm. One hoop layer was then wound at a back tension of 4 kg / bundle and a winding speed of 0.5 m / sec at a pitch of 1.6 cm, and then one helical layer was laminated at an angle of 14 degrees to the liner axis at a pitch of 1.6 cm. This was then cured in a curing oven at 120°C for 11 hours to obtain a pressure vessel for evaluating the breaking strength. Resin Composition: Bisphenol A epoxy resin: 100 parts by mass 4-Methylcyclohexane-1,2-dicarboxylic anhydride ··· 80 parts by mass The bisphenol A type epoxy resin used was EPON828 (trade name) manufactured by Yuka Shell Epoxy Co., Ltd. The 4-methylcyclohexane-1,2-dicarboxylic anhydride used was Lindride52 (trade name) manufactured by LINDAU CHEMICAL INC. The burst pressure (d) of this pressure vessel for evaluating burst strength was measured by applying a water pressure of 45 MPa / sec using a burst test device. This measurement was carried out three times for each Example and Comparative Example, and the average value was calculated and evaluated according to the following criteria. ○: d > 150MPa, △: 150MPa ≧ d > 130MPa, ×:d ≦ 130MPa

[0065] [Example 1] A copolymer spinning dope consisting of 95% by mass of acrylonitrile, 4% by mass of methyl acrylate, and 1% by mass of itaconic acid was wet-spun at a draft ratio of 24% by a conventional method using three spinnerets with 12,000 holes. After washing with water, oiling, and drying, the resulting fiber bundle was steam-drawn to a total draw ratio of 14 times, to obtain a precursor fiber bundle with 36,000 single fibers. The resulting precursor fiber bundle was flame-retarded at a temperature range of 240 to 250°C while being drawn in heated air, to obtain a flame-retardant fiber bundle. The average fiber diameter of the single fibers constituting this flame-retardant fiber bundle was 10.42 μm, the coefficient of variation of the fiber diameter was 5.80%, and the number of single fibers that were 85% of the average fiber diameter, i.e., less than 8.857 μm, was 1.14%. The flame-resistant fiber bundle was carbonized in a nitrogen atmosphere at a temperature range of 300 to 1200°C for 3 minutes, and then surface-treated by electrolytic oxidation in a 10% aqueous solution of ammonium sulfate with an electric charge of 20 C / g, and a sizing agent was applied to obtain a carbon fiber bundle. As the sizing agent, a mixture of 40 mass% epoxy resin, 50 mass% polyester resin, and 10 mass% polyoxyethylene polyoxypropylene block polymer dispersed in water at 2 mass% was used. The amount of the sizing agent attached was 0.8 mass%. The average fiber diameter of the single fibers constituting the carbon fiber bundle was 5.84 μm, the coefficient of variation of the fiber diameter was 5.09%, the number of single fibers less than 85% of the average fiber diameter, i.e., 4.964 μm, was 1.37%, and the resin-impregnated strand strength was 5990 MPa. The abrasion resistance (a / b) of this carbon fiber bundle was 0.05, and the spread width was 0.0225 mm / Tex. In addition, the burst pressure of a pressure vessel made using this carbon fiber was evaluated and found to be 155 MPa.

[0066] [Examples 2 to 4, Comparative Examples 1 to 3] Example 2 was carried out in the same manner as Example 1, except that the draft rate was changed to 30%. Example 3 was carried out in the same manner as Example 1, except that a spinneret with 18,000 holes was used. Example 4 was carried out in the same manner as Example 1, except that a spinneret with 36,000 holes was used. In Comparative Example 1, the same procedure as in Example 4 was carried out except that the draft rate was set to 40%. Comparative Example 2 was carried out in the same manner as in Example 4, except that the draft rate was set to 30%. Comparative Example 3 was carried out in the same manner as in Example 4, except that the draft rate was set to 12%. In Comparative Example 4, the same procedure as in Example 4 was carried out, except that the amount of the sizing agent applied was 1.6 mass %. These results are shown in Table 1.

[0067] [Table 1]

[0068] In Comparative Examples 1 and 2, the draft ratio was high despite the large number of holes in the spinneret. Therefore, in Comparative Examples 1 and 2, the ratio of single fibers having a fiber diameter less than 85% of the average fiber diameter in the flame-resistant fiber bundle exceeded 3.0%. In Comparative Example 3, the draft ratio was low despite the large number of holes in the spinneret. Therefore, the tensile strength of the finally obtained carbon fiber was low. In Comparative Example 4, the spread width was less than 0.0180 mm / Tex, and the burst pressure of the pressure vessel was low. That is, in order to achieve a sufficient burst pressure, it is necessary to narrow the pitch when winding the carbon fiber, which results in an increase in the mass of the pressure vessel. In Comparative Examples 1 and 3, the strength of the obtained carbon fibers was low, and as a result, the burst pressure of the pressure vessel was low. On the other hand, in Comparative Example 2, the strength of the obtained carbon fibers was high. However, since the ratio of single fibers having a fiber diameter less than 85% of the average fiber diameter in the carbon fiber bundle exceeded 3.0%, the abrasion resistance was low and the actual burst pressure of the pressure vessel was low, even though the high-strength carbon fibers were obtained. That is, since the carbon fibers were high in strength, the theoretical burst pressure was high, but the single fibers having a small fiber diameter were cut during filament winding molding, and as a result, the actual burst pressure of the pressure vessel was low. In Comparative Example 4, the strength of the obtained carbon fibers was high. However, since the spread width was less than 0.0180 mm / Tex, although the high-strength carbon fibers were obtained and the abrasion resistance was high, gaps were generated between the carbon fibers when the fiber bundle was wound around the pressure vessel, and therefore the actual burst pressure of the pressure vessel was low. In contrast, in Examples 1 to 4, the number of holes in the spinneret and the draft rate were appropriately combined, and the ratio of single fibers having a fiber diameter less than 85% of the average fiber diameter in the flame-resistant fiber bundle and the carbon fiber was significantly less than 3.0%. Therefore, the abrasion resistance of the carbon fiber bundle was high, and the pressure vessel produced by the filament winding molding method had a high burst pressure.

Claims

1. A carbon fiber bundle having a sizing agent attached thereto, The fineness is 800 to 3000 Tex, The number of single yarns is 20,000 to 50,000, The coefficient of variation of fiber diameter of each single fiber is 10% or less, The ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less, The value obtained by dividing the yarn width (mm) by the fineness (Tex) when rewound under a tension of 1 N is 0.0180 mm / Tex or more; A carbon fiber bundle having a tensile strength of 5,600 MPa or more.

2. 2. The carbon fiber bundle according to claim 1, wherein each of the single fibers constituting the carbon fiber bundle has streaky irregularities on its surface along the fiber axis direction.

3. Knot strength: 600-800N / mm 2 The carbon fiber bundle according to claim 1 or 2, wherein the range is

4. The carbon fiber bundle according to claim 1 or 2, which is for use in filament winding molding.

5. 3. The carbon fiber bundle according to claim 1, which is used as the reinforcing fiber of a pressure vessel having a metal or resin liner whose outer periphery is covered with a fiber-reinforced plastic shell made of reinforcing fibers and resin.

6. By subjecting the carbon fiber precursor fiber bundle to flame retardant treatment, The fineness is 1600 to 6000 Tex, The number of single yarns is 20,000 to 50,000, The coefficient of variation of fiber diameter of each single fiber is 10% or less, Obtaining a flame-resistant fiber bundle in which the ratio of the number of single fibers having a fiber diameter less than 85% of the average fiber diameter is 3.0% or less; 2. The method for producing a carbon fiber bundle according to claim 1, further comprising the step of carbonizing the flame-resistant fiber bundle.

7. The method for producing a carbon fiber bundle according to claim 6, wherein the carbon fiber precursor fiber bundle is produced by a wet spinning method.

Citation Information

Patent Citations

  • Precursor fiber for carbon fiber, method for producing the same and method for producing carbon fiber

    JP2010255159A